"تقدير دالة الإنتاج كوب دوغلاس في الاقتصاد الجزائري خلال فترة: 1990-2020 " - روميصة, بن عبيد; شوقي, جهينة; خديجة, سلطاني (University of eloued جامعة الوادي, 2022)
"الملخص محاولة نمذجة دالة الإنتاج كوب دو غلاس في الإقتصاد الجزائري خلال الفترة 1990 – 2020: تهدف هذه الدراسة إلى التعرف على دالة الإنتاج والمحركات الأساسية لها، وكذلك إلى تقدير و اسقاط ما قمنا بدراسته في الاقتصاد القياسي على الواقع الاقتصادي لوطننا الجزائر، قمنا في هذه الدراسة بالاستعانة بأدوات القياس الكمية الاقتصادية المتمثلة في أسلوب الانحدار الخطي المتعدد بالاعتماد على طریقة المربعات الصغرى ولإخراج النتائج نستعین بالبرنامج الإحصائي EVIEWS 10 ، خلال الفترة 1990 إلى 2020 ، بالاعتماد على المتغيرات الناتج المحلي، الإنفاق الحكومي، رأس المال والعمل . توصلت هذه الدراسة إلى تقدير نموذج دالة كوب دوغلاس، وكذا تحديد مدى مساهمة العوامل (العمل، رأس المال، الانفاق الحكومي) في العملية الانتاجية.. "" Estimation of the production function of Cobb Douglas in the Algerian economy during a period of time : 1990 – 2020 Abstract : This study aims to identify the production function and its main drivers, as well as to estimate and drop what we have studied in econometrics on the economic reality of our homeland Algeria. In this study, we used the help of economic Yuantitative measurement tools represented in the method of multiple linear regression based on the method of least sYuares and for the output Results We use the EVIEWS 10 statistical program, during the period 1990 to 2020, depending on the variables of GDP, government spending, capital and labor. This study reached an estimate of the Cobb Douglas function model, as well as determining the extent to which factors (business, capital, government spending) contribute to the production process . "
ماستر اقتصاد
Keywords: لإنتاج، عوامل الانتاج، دالة الانتاج كوب دوغلاس، النموذج القياسي.; production, factors of production, Cobb Douglas production function